Step-by-step explanation:
65 - 2 × 7 + 9 ÷ 3
65 - 14 + 3
51 + 3 = 54
Option A is the correct answer
Answer:
mean:12
Step-by-step explanation:
1. x=6
2. y=6
3. x=10
4. y=10
1.c+9= 19
2. 9-y=7
3. 5y=30
4. u-u=0
1. 2(3x2 - 5x3)
2(6-15)
2x(-9)=18
<span>2y = x + 3 then x = 2y - 3
5y = x - 7 then x = 5y + 7
so
</span>2y - 3 = 5y + 7
2y - 5y = 7 + 3
-3y = 10
y = -10/3
y = -3 1/3
<span>2y = x + 3
</span>2 (-10/3) = x + 3
-20/3 - 3 =x
-29/3 = x
-9 2/3 =x
or
x = -9 2/3
solutions: x = -9 2/3 and y = -3 1/3
I can’t find the answer. Are you sure this is the whole question?